Differential inhibition of α-synuclein oligomeric and fibrillar assembly in parkinson's disease model by cinnamon extract - Shaltiel-Karyo, Ronit; Davidi, Dan; Frenkel-Pinter, Moran; Ovadia, Michael; Segal, Daniel; Gazit, Ehud (Biochimica et biophysica acta, 2012)
The oligomeriztion of α-synuclein (α-syn) into ordered assemblies is associated with the symptoms of Parkinson's Disease (PD). Yet, it is still debatable whether oligomers are formed as part of a multistep process towards amyloid fibril formation or alternatively as "off-pathway" aggregates. 100μM α-syn was incubated with decreasing amounts of cinnamon extract precipitation (CEppt). The fibril formation was measured using spectroscopy and microscopy analyses and oligomers were detected using western blot analysis. The secondary structure of the protein was analyzed using CD. Drosophila brains were studied using immunostaining and confocal microscopy. Here we probed the inhibition pattern of oligomeric and fibrillar forms of α-syn, using a natural substance, CEppt which was previously shown to effectively inhibit aggregation of β-amyloid polypeptide. We demonstrated that CEppt has a differential inhibitory effect on the formation of soluble and insoluble aggregates of α-synuclein in vitro. This inhibition pattern revokes the possibility of redirection to "off-pathway" oligomers. When administering to Drosophila fly model expressing mutant A53T α-syn in the nervous system, a significant curative effect on the behavioral symptoms of the flies and on α-syn aggregation in their brain was observed. We conclude that CEppt affects the process of aggregation of α-syn without changing its secondary structure and suggest that increasing amounts of CEppt slow this process by stabilizing the soluble oligomeric phase. When administered to Drosophila fly model, CEppt appears to have a curative effect on the defective flies. Our results indicate that CEppt can be a potential therapeutic agent for PD. ► We show that CEppt is an effective inhibiter for α-synuclein aggregation. ► CEppt has a differential effect on the formation of soluble and insoluble aggregates. ► High molecular ratio of CEppt stabilizes oligomers. ► Drosophila model shows reduced brain aggregates and defective phenotype correction.